Subpopulations in aMPV vaccines are unlikely to be the only cause of reversion to virulence. Issue 21 (15th May 2015) - Franzo, G.; Naylor, C.J.; Drigo, M.; Croville, G.; Ducatez, M.F.; Catelli, E.; Laconi, A.; Cecchinato, M.
Highlights Development of different NGS protocols for aMPV full genome sequencing. First study investigating aMPV vaccine subpopulation using NGS. Comparison of identified SNV with attenuation/reversion to virulence markers. Evidence of the role of intra-vaccine variability in vaccine reversion to virulence.